2021
DOI: 10.1021/acs.energyfuels.1c01477
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Coal-Nitrogen Release and NOx Evolution in Oxygen-Enriched and Deep-Staging Combustion

Abstract: Oxygen-enriched and deep-staging (OE and DS) combustion has drawn increasing attention due to its superior nitrogen oxide reduction efficiency and combustion efficiency. To clarify the NO x generation and burnout characteristics of coal in OE and DS combustion, the effects of temperature, oxygen concentration, and stoichiometric ratio in the fuel-rich zone (SR1) on conversions of coal nitrogen and char in fuel-rich (FR) and fuel-lean (FL) zones were experimentally studied in a drop-tube furnace. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Daood et al 23 found that oxygen-enriched combustion reduced NO emissions and improved carbon burnout. Zhu et al 24 found that high temperature promoted NO x formation in FR (fuelrich) zone, and under staging conditions, the increase of oxygen concentration can reduce NO x generation in the FR (fuel-rich) zone and FL (fuel-lean) zone. On the contrary, Lei et al 25 found that when coal is burned in an oxygen-rich atmosphere, SO 2 emissions are reduced under different pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Daood et al 23 found that oxygen-enriched combustion reduced NO emissions and improved carbon burnout. Zhu et al 24 found that high temperature promoted NO x formation in FR (fuelrich) zone, and under staging conditions, the increase of oxygen concentration can reduce NO x generation in the FR (fuel-rich) zone and FL (fuel-lean) zone. On the contrary, Lei et al 25 found that when coal is burned in an oxygen-rich atmosphere, SO 2 emissions are reduced under different pressures.…”
Section: Introductionmentioning
confidence: 99%